2016
DOI: 10.1590/bjpt-rbf.2014.0152
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory factor analysis for differentiating sensory and mechanical variables related to muscle-tendon unit elongation

Abstract: BackgroundStretching exercises are able to promote adaptations in the muscle-tendon unit (MTU), which can be tested through physiological and biomechanical variables. Identifying the key variables in MTU adaptations is crucial to improvements in training.ObjectiveTo perform an exploratory factor analysis (EFA) involving the variables often used to evaluate the response of the MTU to stretching exercises.MethodMaximum joint range of motion (ROMMAX), ROM at first sensation of stretching (FSTROM), peak torque (to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
3
9
0
Order By: Relevance
“…According to our results, 30 seconds of stretching by PNF method is already enough to occasion sensibility decrease in muscular proprioceptors, tendinous and articular, as well as in nociceptors, that constitute fundamental mechanisms for protection and organization of structures related to human movement, such strength reduction after stretching in different insistence times can be, partially, explained by an autogenic inhibition and reciprocal inhibition caused by stretching due to Golgi tendon organs activation that can cause decrease in alpha motoneurons excitability. However, corroboring with Chagas et al [9], we recommend further studies involving the long-term effects of stretching using different stretching methods and neurophysiological variables. In summary, it was verified that acutely stretching method by PNF causes reduction on muscular isometric strength of muscles involved in manual grip.…”
Section: Crimson Publisherssupporting
confidence: 86%
“…According to our results, 30 seconds of stretching by PNF method is already enough to occasion sensibility decrease in muscular proprioceptors, tendinous and articular, as well as in nociceptors, that constitute fundamental mechanisms for protection and organization of structures related to human movement, such strength reduction after stretching in different insistence times can be, partially, explained by an autogenic inhibition and reciprocal inhibition caused by stretching due to Golgi tendon organs activation that can cause decrease in alpha motoneurons excitability. However, corroboring with Chagas et al [9], we recommend further studies involving the long-term effects of stretching using different stretching methods and neurophysiological variables. In summary, it was verified that acutely stretching method by PNF causes reduction on muscular isometric strength of muscles involved in manual grip.…”
Section: Crimson Publisherssupporting
confidence: 86%
“…Although ROM MAX and TOR MAX present a positive moderate correlation ( r = .69, P < .001), the common variance relative to the factors influencing these variables was less than 50% ( r 2 x 100). Chagas et al found that ROM MAX and TOR MAX fitted to the sensory and mechanical theories, respectively, as described by Weppler and Magnusson . Therefore, the determination of these variables seems to be established by distinct aspects.…”
Section: Discussionmentioning
confidence: 90%
“…They passed independently by all experimental conditions randomized by drawing lots. Flexibility variables were measured during stretching maneuvers in a dynamometer isokinetic soon before and after intervention with different mechanical vibration stimulus configurations. All tests were performed by the same examiner at the same period of the day to standardize the effects of circadian rhythm …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations